Endoscopic full-thickness resection of duodenal lesions—a retrospective analysis of 20 FTRD cases - Bauder, Markus (United European Gastroenterol J, 2018)
BACKGROUND: Endoscopic resections in the duodenum harbor a significant risk of complications. The full-thickness resection device (FTRD) has shown favorable results concerning efficacy and safety in the resection of colorectal lesions. Data of its use in the duodenum are limited to a single, small case series (n = 4). METHODS: Data of all consecutive patients scheduled for endoscopic full-thickness resection (EFTR) of duodenal lesions by FTRD in our institution were collected and analyzed retrospectively. Primary endpoint was technical success. RESULTS: Between March 2014 and June 2017 EFTR of a duodenal lesion was planned in a total of 20 patients. Overall technical success was 17/20 (85.0%). Indication for EFTR was: adenomas (n = 13, seven treatment naïve, six pretreated), subepithelial tumors (n = 5) and T1 adenocarcinoma (n = 1). The FTRD could be advanced to the lesion in 19/20 cases (95.0%). R0-resection rate was 12/19 (63.2%). During follow-up after 3 and 12 months there were two recurrent adenomas that were successfully re-resected by FTRD. Minor bleedings occurred at the first postinterventional day in 3/19 (15.8%). There were no major bleedings and perforations. CONCLUSION: This study confirmed the feasibility of duodenal EFTR and indicates good efficacy and safety. Larger studies are needed to further investigate this novel technique.